Macroscopic material degradation model of Norway spruce clear wood for XFEM - Tamás Király; Zsolt Karácsonyi; Rudolf Polgár (Results in Materials, 2023)
The study aims at investigating the failure behavior of Norway spruce clear wood specimens using XFEM by modeling earlywood and latewood growth rings. The growth ring pattern in the specimens are determined using a photo-analytical processing program. For the simulations, 6 damage initiation mechanisms were considered and the subroutines were implemented in the finite element solver ABAQUS. A normal vector to the crack surface is calculated for each damage mode, taking into account the orientation of the maximum and minimum principal stresses. The XFEM model and the material properties are calibrated based on experiments, where the edge-notched specimens were subjected to 3-point bending, tensile and compression tests. The goal is to determine the ultimate load, locate structural weakpoints and obtaining a realistic crack propagation path by means of XFEM.